Evaluating implementation of a fire-prevention injury prevention briefing in children's centres: cluster randomised controlled trial - Deave, Toity; Hawkins, Adrian; Kumar, Arun; Hayes, Mike; Cooper, Nicola; Watson, Michael; Ablewhite, Joanne; Coupland, Carol; Sutton, Alex; Majsak-Newman, Gosia; McDaid, Lisa; Goodenough, Trudy; et al. (Public Library of Science, 2017)
Background: Many developed countries have high mortality rates for fire-related deaths in children aged 0–14 years with steep social gradients. Evidence-based interventions to promote fire safety practices exist, but the impact of implementing a range of these interventions in children’s services has not been assessed. We developed an Injury Prevention Briefing (IPB), which brought together evidence about effective fire safety interventions and good practice in delivering interventions; plus training and facilitation to support its use and evaluated its implementation.